Brain organoids, consciousness, ethics and moral status. (30th July 2023) - Jeziorski, Jacob; Brandt, Reuven; Evans, John H.; Campana, Wendy; Kalichman, Michael; Thompson, Evan; Goldstein, Lawrence; Koch, Christof; Muotri, Alysson R.
Abstract: Advances in the field of human stem cells are often a source of public and ethical controversy. Researchers must frequently balance diverse societal perspectives on questions of morality with the pursuit of medical therapeutics and innovation. Recent developments in brain organoids make this challenge even more acute. Brain organoids are a new class of brain surrogate generated from human pluripotent stem cells (hPSCs). They have gained traction as a model for studying the intricacies of the human brain by using advancements in stem cell biology to recapitulate aspects of the developing human brain in vitro . However, recent observation of neural oscillations spontaneously emerging from these organoids raises the question of whether brain organoids are or could become conscious. At the same time, brain organoids offer a potentially unique opportunity to scientifically understand consciousness. To address these issues, experimental biologists, philosophers, and ethicists united to discuss the possibility of consciousness in human brain organoids and the consequent ethical and moral implications.